PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN (STUDI PADA RUMAH MAKAN BAKMI TUNGKU DI KABUPATEN BADUNG) - Putra, Fahrainsyah Wahyu; Sulistyawati, Eka (E-Jurnal Manajemen; Vol 7 No 1 (2018), 2018)
This study aims to explain the effect of service quality on customer satisfaction and customer loyalty, the influence of customer satisfaction on customer loyalty, and the role of customer satisfaction mediate the quality of service to customer loyalty. This research was conducted at Rumah Makan Bakmi Tungku Uluwatu, Jimbaran with the population that is used by all customers in Rumah Bakmi Tungku Uluwatu, Jimbaran which visited before and the sample size of 100 people, the calculation of the indicator number multiplied 5 to 10. Data collection is done by spreading questionnaire and using Likert scale to measure 21 indicators from three research variables. Analysis technique used in this research is path analysis (path analysis). The results of this study indicate that the quality of service has a positive and significant impact on customer loyalty, service quality has a positive and significant impact on customer satisfaction, and customer satisfaction has a positive and significant impact on customer loyalty. The results also show that customer satisfaction is able to mediate the influence of service quality on customer loyalty.